Regulation of Voltage-Activated K+ Channel Gating by Transmembrane β Subunits - Sun, Xiaohui; Zaydman, Mark A.; Cui, Jianmin (Frontiers in Pharmacology, 2012)
Voltage-activated K+ (KV) channels are important for shaping action potentials and maintaining resting membrane potential in excitable cells. KV channels contain a central pore-gate domain (PGD) surrounded by four voltage-sensing domains (VSD). The VSDs will change conformation in response to alterations of the membrane potential thereby inducing the opening of the PGD. Many KV channels are heteromeric protein complexes containing auxiliary β subunits. These β subunits modulate channel expression and activity to increase functional diversity and render tissue specific phenotypes. This review focuses on the KV β subunits that contain transmembrane (TM) segments including the KCNE family and the β subunits of large conductance, Ca2+- and voltage-activated K+ (BK) channels. These TM β subunits affect the voltage-dependent activation of KV α subunits. Experimental and computational studies have described the structural location of these β subunits in the channel complexes and the biophysical effects on VSD activation, PGD opening and VSD-PGD coupling. These results reveal some common characteristics and mechanistic insights into KV channel modulation by TM β subunits.